ZIKV prM hijacks PIM1 kinase for phosphorylation to prevent ubiquitin−mediated degradation and facilitate viral replication - Ren, Yingying; Liu, Yishuo; Pang, Rui; Xu, Gang; Lei, Yining; Kwok, Hang Fai; Wu, Yingliang; Cao, Zhijian (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionViral infection usually stimulates a variety of host cell factors to modulate the life cycle of the virus. PIM1, a serine/threonine protein kinase widely involved in cell proliferation, survival, differentiation and apoptosis, was recently reported to be upregulated by Zika virus (ZIKV) infection. However, how ZIKV-PIM1 interactions affect the viral life cycle are not fully understood.Methods and resultsHere, we demonstrated that ZIKV replication was suppressed by the PIM1 kinase inhibitor SGI-1776 in both wt and Ifnar1-/- murine peritoneal macrophages, indicating that PIM1 functions independently of type I IFN signaling. Co-immunoprecipitation and GST pull-down assays revealed that the ZIKV structural protein precursor membrane (prM) interacted with PIM1. Moreover, we found that prM protein stability was enhanced by PIM1, which was attributed to its kinase activity. Mechanistically, we revealed that prM can undergo ubiquitin‒mediated proteolysis and the E3 ubiquitin ligase AMFR can target prM for degradation. Importantly, PIM1 catalyzed phosphorylation of prM at Ser101 and Thr107, and this phosphorylation prevented the proteasome-dependent degradation of prM by impairing its association with AMFR. Therefore, the S101/T107-D phosphorylation mimic mutant of prM was more resistant to PIM1-induced increases in cellular abundance.DiscussionThese findings revealed PIM1 as a critical host factor that is advantageous to ZIKV and revealed that targeting the PIM1‒prM axis is a conducive strategy for controlling ZIKV infection.